Lectotypification and taxonomic reinstatement of Syzygium benthamianum (Myrtaceae) - Shareef, S.m.; Beegam, A. Rasiya; Byng, James W (Phytotaxa, 2020)
The species status of Syzygium benthamianum is reinstated and a lectotype is designated.